Evolution of Stenotrophomonas maltophilia in Cystic Fibrosis Lung over Chronic Infection: A Genomic and Phenotypic Population Study - Esposito, Alfonso; Pompilio, Arianna; Bettua, Clotilde; Crocetta, Valentina; Giacobazzi, Elisabetta; Fiscarelli, Ersilia; Jousson, Olivier; Di Bonaventura, Giovanni (Frontiers in Microbiology, 2017)
Stenotrophomonas maltophilia has been recognized as an emerging multi-drug resistant opportunistic pathogen in cystic fibrosis (CF) patients. We report a comparative genomic and phenotypic analysis of 91 S. maltophilia strains from 10 CF patients over a 12-year period. Draft genome analyses included in silico Multi-Locus Sequence Typing (MLST), Single-Nucleotide Polymorphisms (SNPs) and pangenome characterization. Growth rate, biofilm formation, motility, mutation frequency, in vivo virulence, and in vitro antibiotic susceptibility were determined and compared with population structure over time. The population consisted of 20 different sequence types (STs), 11 of which are new ones. Pangenome and SNPs data showed that this population is composed of 3 major phylogenetic lineages. All patients were colonized by multiple STs, although most of them were found in a single patient and showed persistence over years. Only few phenotypes showed some correlation with population phylogenetic structure. Our results show that S. maltophilia adaptation to CF lung is associated with consistent genotypic and phenotypic heterogeneity. Stenotrophomonas maltophilia infecting multiple hosts likely experiences different selection pressures depending on the host environment. The poor genotype-phenotype correlation suggests the existence of complex regulatory mechanisms that need to be explored in order to better design therapeutic strategies.